The artist as historian, strategies against the erasure of memory - (:unkn) unknown (My University, 2019)
If history is what was collectively decided to be remembered, artists often emphasize what was collectively decided to be forgotten. Susan Sontag summed up the attitude of many contemporary artists who propose an alternative to the narrative of the dominant history, which was often written by the victors, by freely using the tools of the "historian". The artist Kader Attia highlights both the wound and the healing process while Jean-François Boclé dictates the Black Code in a performance piece. Without becoming true historians, artists symbolically attempt to heal "postcolonial melancholy" and propose different strategies against forgetfulness or denial of memory. These questions are currently back on the table in the light of discussions concerning the restitution of objects to Africa by Western museums.
Keywords: African Research